A Sociolinguistics Analysis Of Register Used In Online Shop Of Social Media (www.facebook.com) - Nur Alfi, Farikha, Drs. Maryadi. M.A, Siti Fatimah, SPd, M. Hum (2013)
Language used in online shop is different from that used by people in daily conversation. There are specific terms to explain the event that happens in online shop. Many registers used in online shop can be found especially in English. In this case, this research analyzes the linguistics form and the meaning of register used in online shop. The type of this research is descriptive qualitative research. The object of this research is the register used in online shop. The data are register words and phrases included in printed material used in online shop. The data source is dialogue between the buyer and seller in online shop. In collecting the data, the writer looks for the dialogue in online shop, reads the dialogue repeatedly, gives a sign to the register words, and writes down the dialogue, register words, and phrases. In analyzing the data, the writer classifies the data, analyzes the linguistics form and meaning, analyzes the context of situation, identifies the differences between lexical and contextual meaning and draws conclusion. Based on the analysis, the researcher finds the data based on the linguistics form (7 data of verb, 3 data of noun, 1 datum of adjective, 8 data of compound word, 5 data of abbreviation, and 2 data of noun phrase). Based on the meaning, the writer finds 16 data in contextual meaning and 10 data in lexical meaning.